Components and Criteria of Continuous Education Based on Local Potential in Vocational Education: A Literature Review - Muhammad Ripqi Lubis; Isma Widiaty; Yatti Sugiarti (VANOS Journal of Mechanical Engineering Education, 2026)
The Sustainable Development Goals (SDGs) requires a transformation in Technical and Vocational Education (TVET) through the integration of local wisdom with sustainability principles. However, existing research show fragmentation conceptual between literacy environment, skills green, and conservation culture without framework comprehensive work. This research aim for identify component main and criteria sustainable TVET curriculum based potential local as well as analyze the relationship between both of them. Review literature narrative done against 18 articles quality high (2019–2025) from the Scopus database, analyzed through analysis thematic and mapping draft assisted intelligence artificial. Research results reveals 10 core components that cover 52 criteria specific, with wisdom local as knot main connecting education vocational sustainable and skills sustainability. Literacy sustainability appear as most dominant component with 8 criteria, followed by a development model curriculum and utilization potential local (6 criteria each). Framework Work curriculum based on the proposed cultural-pedagogical nexus give runway theoretical-practical for development inclusive TVET curriculum, advancing Education for Sustainable Development (ESD) through integration systematic system knowledge local with modern pedagogy. Fifth tens two criteria measurable this can implemented for evaluation curriculum and formulation policies in TVET institutions.